Evaluation of two stable internal fixation techniques in mandibular ramus sagittal osteotomy: a three-dimensional finite element study - Silva, Kaline de Moura; Machado, Leonardo Mendes Ribeiro; Leite, Milena Gomes Melo [UNESP]; Noritomi, Pedro Yoshito; de Jesus, Giorge Pessoa; de Moura, Andrezza Lauria (Springer Nature, 2025)
Purpose: To evaluate and compare, using finite elements three-dimensional (3D) analysis, two techniques of stable internal fixation in 2 patterns of sagittal split ramus osteotomy (SSRO) and the repercussions of occlusal load distribution in the postoperative period. Methods: A 3D finite element model of a hemimandible was created. The models were divided into 2 split patterns of SSRO advanced 5 mm forward, a split pattern (1) following the Epker osteotomy design and another split pattern (2) following Posnick osteotomy design, simulated by CAD (Computer Aided Engineering) Rhinoceros 3D®. Two internal fixation techniques were simulated by HyperMesh: A– one titanium miniplate of the Arnett system (1 mm) for orthognathic surgery fixed with four monocortical screws; B– one titanium plate fixed with four monocortical screws and one bicortical screw. Resistance, stress and displacement were analyzed applying a 200 N vertical load to the occlusal surface region of the mandibular first molar and a 100 N to the incisal surface of the mandibular central incisor. Results: The results were presented through the von Mises stress analysis. A difference in the displacement of the models fixed with only one miniplate and four monocortical screws was observed. The models with split pattern (2) presented smaller displacements when compared to the split pattern (1). For metallic components, the split pattern (2) exhibits lower strain values, although it has no significant difference. Conclusion: The fixation technique B proved to be more rigid and lower stress values both in the bone and in the plate, as well as lower deformation and displacements were shown in comparison to fixation technique A for all mandibular movements and forces.
Keywords: Finite element analysis; Internal fixation device; Mandibular osteotomy; Orthognathic surgery